Factores que influyen en los embarazos a temprana de edad en las jóvenes entre los 12 y 20 años en un barrio del distrito turístico de Riohacha (2021)
The present study aimed to explore the factors that influence early pregnancy in young women between the ages of 12 and 20 in the Villa Fátima neighborhood of the Riohacha Tourist District, with a qualitative approach and a grounded theory design was implemented. an interview with a sample of 10 young people in a state of pregnancy. No direct influence was detected from friends and family, they mentioned that the baby was the product of ignorance. On the other hand, they expressed having some basic knowledge about STDs and contraceptive methods, but ignorance on the subject of sexuality could influence their premature pregnancy